Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1966
DOI: 10.1128/jb.91.3.1070-1079.1966
|View full text |Cite
|
Sign up to set email alerts
|

Inoculum-Dependent Division Lag of Bacillus Cultures and Its Relation to an Endogenous Factor(s) (“Schizokinen”)

Abstract: Inoculum-dependent division lag of Bacillus cultures and its relation to an endogenous factor(s) ("schizokinen").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 12 publications
(5 reference statements)
2
25
0
Order By: Relevance
“…The finding that piliated, virulent Ti gonoad to contain high levels of cell-associated cocci produced more gonobactin than did the ng agent. Sonic lysates of B. megaterium nonpiliated T3 strains was interesting and conin low-iron medium contained significant sistent with our observations that piliated gonkts of SK (6,13). Synthesis of an unknown ococci were more virulent and better able to camate by E. coli carrying the Col V vir-acquire iron in the chicken embryo model (19).…”
Section: Gitidis Ysis Of the Cells Other Microbes Have Beensupporting
confidence: 70%
“…The finding that piliated, virulent Ti gonoad to contain high levels of cell-associated cocci produced more gonobactin than did the ng agent. Sonic lysates of B. megaterium nonpiliated T3 strains was interesting and conin low-iron medium contained significant sistent with our observations that piliated gonkts of SK (6,13). Synthesis of an unknown ococci were more virulent and better able to camate by E. coli carrying the Col V vir-acquire iron in the chicken embryo model (19).…”
Section: Gitidis Ysis Of the Cells Other Microbes Have Beensupporting
confidence: 70%
“…Production of catechols by E. coli. The inoculum-dependent growth of Bacillus megaterium in low-iron medium can be overcome by the addition of its own culture fluid, which contains an iron-binding hydroxamate (19). Preliminary experiments showed that 7-h broth culture fluid exerted a similar effect on E. coli 0141 in serum, suggesting that a product of bacterial metabolism was required for growth in serum.…”
Section: Resultsmentioning
confidence: 99%
“…In several systems that were investigated it was further shown that the lag phase could be shortened and growth initiated by addition of small molecules, such as CO2 (9), specific amino acids (6), Krebs cycle intermediates (18), and kojic acid (16). More significantly, Bacillus megaterium was shown to accumulate an ironchelating hydroxamic fcid during the lag phase of growth (17). This diffusible endogenous siderochrome (1) overcame the inoculum-dependent lag of B. megaterium (2) and Bacillus subtilis (16).…”
Section: Discussionmentioning
confidence: 99%